Estabilidade em edifícios de concreto armado com pavimentos em lajes planas - Cicolin, Luiz Antonio Betin (Universidade Federal de São Carlos, 2007)
This present work covers possible manners of evaluating steel concrete frames designed for multiple flooring buildings as far as instability and necessity of second order efforts are concerned. Starting from single floor projects with simple flat slab frame, models with different numbers of floors are considered. The models do not use large rigidity elements such as staircases and lift shafts. The modeling used in this piece adopts simplified criteria for vertical action dimensioning, forming frames with flat slab layers taken as low height beams. These models are evaluated. Based on the results, the work analyzes the application validity of criteria to dismiss consideration of the NBR6118:2003 code presented second order global effort, and compares this against the P-∆ process utilization. Results both with and without inverted beams at the periphery are compared.
Keywords: Concreto armado.; Lajes lisas em concreto armado; Instabilidade; Lajes cogumelo; Edifícios em lajes lisas; Instability; Second order efforts; Flat slabs; Mushroom type slabs; Steel concrete: Flat slab buildings; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL